IN-VIVO CHARACTERIZATION OF TOTAL PROTEIN, ALBUMIN CONTENT, LIPID PROFILE AND ENZYMATIC PROPERTY OF BALAJIRAKADI KVATHA CURNA (BLJ) IN ALBINO RAT PLASMA - Rahman Bhuiyan, Jamilur; Biswas, Sujit; Dutta, Saugata; Abdullah-Al-Mamun, Md.; Huque, Amdadul; K Choudhuri, Shahabuddin (International Journal of Ayurveda and Pharma Research, 2015)
The study was devised to evaluate the effect of total protein, albumin content, enzymatic property and lipid profile in rats plasma after chronic administration of Balajirakadi Kvatha Curna (BLJ), a classical Ayurvedic preparation that is widely used in cough. The drug was administered per oral route at a dose of 40 ml/kg of the body weight for 45 consecutive days. Eight-week old albino rats (Rattus novergicus : Sprague - Dawley strain,) of both sexes, bred and maintained at the Animal House of the Department of Pharmacy, Jahangirnagar University were used for the experiment. All experiments on rats were carried out in absolute compliance with the ethical guide for care and use of laboratory animals. After the administration of BLJ preparation for a period of 45 days, the following biochemical parameters (protein, albumin, triglyceride, cholesterol, LDL, VLDL, HDL, sGPT sGOT and ALP) in the plasma of both the male and female rats were determined. An increased level of Total protein, the Albumin content and triglyceride in the plasma found in the both male and female rats, none of these changes were significantly different from their corresponding control values but noticeable. On the contrary in both female and male rats the decreased level in the total Cholesterol, VLDL, LDL and HDL was noticed and among which Total Cholesterol and VLDL are significant. Surprisingly the LDL content was almost similar to the corresponding control value and decrease in HDL was not significant. A statistically very highly significant increase in the sGPT sGOT and ALP activities in the plasma of male rats was found while in the female rats it has been showed a statistically very highly significant decrease in sGPT and sGOT but ALP activities in the plasma was statistically insignificant.